Karakteristik Asas Kebebasan Berkontrak dalam Perjanjian Berbasis Syariah - Muhammad Sjaiful (Perspektif Hukum, 2015)
Sharia-based contract is an agreement that is derived from the nomenclature of Islamic law. It is definitely designed as the agreement that shall refer to norms based on legal sources of Islam, i.e. the Qur'an and the Hadith of the Prophet Muhammad. This paper discusses the main issue as follows: the dynamics of developments and characteristic principle of freedom of contract in Sharia-Based Agreement". The research refers to the legal writing i.e. normatively legal research which the issue is conceptually approached. Through this approach, the author wants to explore and formulate the concept of freedom of contract principle in Sharia-based agreements, both in terms of its growth and characteristics. The result of the research shows that characteristics of the principle of freedom of contract in Sharia-Based Agreement contain the basic paradigm based on a philosophical view of divinity and apocalyptic. The meaning is that the principle of sharia-based agreement is not established on absolute freedom of contract, but on the freedom that does not violate Islamic values. Therefore, the principle of freedom of contract in the Sharia-based agreement functionates to ensure the engagement of the parties in obeying the agreement, because in the Islamic perspective, the freedom of contract as a form of agreement among parties to enter into a contract fundamentally becomes the principle for the parties to obey or comply the contract.